Cardiovascular responses to isometric hand grip vs. relaxed hand grip in sustained cycling efforts - Canivel, R. G.; Wyatt, F. B.; Baker, J. S. (The Journal of Strength and Conditioning Research, 2012)
Peripheral isometric contractions may lead to enhanced performance. Previous research using hand grip protocols indicates increased stabilization and peak power outputs. Research is lacking with the grip vs. no-grip protocol during sustained efforts. The purpose of this study is to determine cardiovascular reactions (i.e., heart rate [HR], blood pressure [BP], and rate pressure product [RPP]) during sustained cycling via an isometric and relaxed hand grip. Nine (n = 9) recreational cyclists participated in this study. After signing a medical and physical readiness questionnaire, the subjects were randomly assigned to 1 of 2 different protocols. Preexercising values of the HR (beats per minute), BP (miilimeters of mercury), height (centimeters), weight (kilograms), and age (years) were assessed before testing. A Monark bicycle ergometer was used for testing. Grip was substantiated through the use of a hand grip dynamometer at 20 kg of tension. Protocol 1 used an isometric "Hand Grip" scenario at 150 W for 20 minutes. Protocol 2 used a "Relaxed Hand Grip" at the same power and time. During the 20-minute exercise test, HR (POLAR), BP (stethoscope and sphygmomanometer), and calculated RPP (HR × systolic BP [SPB]/100) were recorded every minute. Statistical measures included mean and SDs between protocols, and dependent samples t-tests were used to examine differences between grip and no-grip protocols. At an alpha of ?0.05, SBP did show a significant increase when using no grip, 161.4 (5.1) mm Hg vs. grip, 154.1 (6.6) mm Hg. However, rate pressure product and heart rate showed no significant differences between protocols. Our data suggested that the use of an isometric hand grip is transient and diminishes over time.